The effect of IT affordance and social commerce constructs on intention to buy: trust and flow experience as mediators - Debora Kristina Silalahi; Ignatius Heruwasto (President University, 2022)
The development of information and technology has encouraged the increase and the importance of social media, it can be seen with the rising trend of online shopping through social media, in this case, Social Commerce emerged as an evolution of traditional E-Commerce. Social media technology and Social Commerce enable commercial activities that take advantage of the interaction function of social media. In Social Commerce, trust and experience of user interaction are important factors that influence users in making decisions. Users build trust and engage in shopping activities on social commerce by easily finding important information needed through other consumer ratings, comments, and recommendations. This research is a quantitative study using primary data through an online survey of 229 respondents who use Facebook in Indonesia and never purchased a fashion product. This study shows that visibility, forums and communities, and ratings and reviews have a positive effect on trust. In contrast, metavoicing, shopping guidance, ratings and reviews, recommendations and referrals do not affect trust. Visibility, metavoicing, guidance shopping and forums and communities positively affect flow experience, while ratings and reviews, recommendations and referrals do not affect flow experience. In this study, trust and flow experience positively affect purchase intention. It is hoped that this research can help optimize the use of social commerce by considering impact it-affordance and social commerce constructs.